UNODA Occasional Papers No. 30, November 2017 - United Nations (United Nations, 2018)
This publication considers lethal autonomous weapon systems, approaching the issue from five different perspectives. It has been published ahead of the first meeting of the Group of Governmental Experts of the High Contracting Parties to the Convention on Certain Conventional Weapons mandated to examine issues related to emerging technologies in the area of lethal autonomous weapon systems in the context of the objectives and purposes of the Convention. The United Nations Office for Disarmament Affairs Occasional Papers are a series of ad hoc publications featuring, in edited form, papers or statements made at meetings, symposiums, seminars, workshops or lectures that deal with topical issues in the field of arms limitation, disarmament and international security.